2007
DOI: 10.1007/s11661-007-9309-0
|View full text |Cite
|
Sign up to set email alerts
|

Phase Stability and Transformations in the Zr2Ni x Cu1−x Amorphous System

Abstract: Since Ni and Cu differ by only one valence electron, yet have nearly identical atomic sizes (1.27 vs 1.28 Å for Cu and Ni, respectively), the amorphous Zr 2 Ni x Cu 1-x system is ideal for isolating the effects of electronic structure on short-and medium-range order and the concomitant influence of both the structure and order on devitrification pathways. Thermal analysis, timeresolved high-energy X-ray diffraction (HEXRD), and transmission electron microscopy (TEM) were used to follow metastable and stable cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…A more negative Zr-Ni interaction parameter should result in the enthalpy minimization routine favoring a relatively greater phase width for the c16 (Zr 2 Ni) structure as compared to the c11b (Zr 2 Cu) structure. This has already been verified experimentally by Kramer et al [45]. This indicates that at least in this system, the electronic structure plays an important role in GFA, a fact ignored in other parameterization schemes.…”
Section: Crystallization Pathways In Metallic Glassessupporting
confidence: 77%
See 1 more Smart Citation
“…A more negative Zr-Ni interaction parameter should result in the enthalpy minimization routine favoring a relatively greater phase width for the c16 (Zr 2 Ni) structure as compared to the c11b (Zr 2 Cu) structure. This has already been verified experimentally by Kramer et al [45]. This indicates that at least in this system, the electronic structure plays an important role in GFA, a fact ignored in other parameterization schemes.…”
Section: Crystallization Pathways In Metallic Glassessupporting
confidence: 77%
“…Experimental studies on crystallization behavior of Zr 2 Cu 1−x Ni x metallic glasses have shown that the Zr 2 Ni (c16) based phase crystallizes for x ≤ 0.625 [45,46]. In the range 0.625 ≤ x ≤ 0.375, both Zr 2 Cu and Zr 2 Ni based phases can be observed, while for x ≤ 0.375 Zr 2 Cu (c11b) is the preferred phase.…”
Section: Crystallization Pathways In Metallic Glassesmentioning
confidence: 99%
“…Studies of simpler Zr-based binary alloys have been more successful, providing important insights into the role of local atomic structures in dictating the transformation pathways and supercooling potential for a liquid. 11 It has been reported that Zr 80 Pt 20 can be quenched into the amorphous state by meltspinning 12,13 and that the X-ray diffraction patterns of the glassy ribbons show a pre-peak near 1.7 Å -1 . 14 Studies of Zr x Pt 100-x (73 ≤ x ≤ 77) glasses 15 show that the intensity of the pre-peak increases with increasing Pt concentration, suggesting that it arises from Pt-Pt correlations.…”
Section: Introductionmentioning
confidence: 99%
“…These alloys also form the basis of more complex alloys with better GFA. Zr-Ni liquids and glasses have been extensively studied by X-ray [20][21][22][23][24] and neutron scattering [13,22,[25][26][27][28][29][30], as well as through simulations [21,[31][32][33]. The results from these studies have attracted attention because of the evidence for significant chemical ordering in both the liquid and glass [21,22,31,33].…”
Section: Introductionmentioning
confidence: 99%